Criminal Response to Crimes Stemming from the Use of Deepfake Technology - Sahar Fouad Majeed Al- Najar (Journal of Legal Sciences, 2024)
Cybercrime is rapidly evolving as technology advances and reaches new dimensions in a way that blurs the lines between what is real and what is simulated. Deepfake technology has become part of cybercrime. Deepfake technology has similar features to CGI technology (Computer Generated Image) in the film industry, making it possible to create videos - images and audio using artificial intelligence arms in a way that is so realistic and difficult for humans to recognize it as fake. This poses serious risks, with potential consequences ranging from unfair electoral practices to the use of forged evidence in court. This technology first emerged in 2017 on a social media platform called Reddit. Although this technology has many legitimate uses, its illegitimate uses are more prominent, resulting in the infringement of legally protected interests. Therefore, the emergence of this technology calls for serious thinking about the serious violations of legally protected interests. Therefore, the criminal legislature must re-adapt the legal rules with a realistic-material meaning, in order to deal with an intangible virtual reality and attempt to criminalize the behaviors resulting from this technology. In addition, the legislature must pay attention to the policies of prevention and protection from crimes arising from deepfake.